Perbedaan antara atap miring dan atap datar dalam menghadapi iklim di Indonesia - Fauzi, Roikhan Amin (Maliki Interdisciplinary Journal, 2024)
Roof is an important element in the architecture of a building. The choice of roof shape in architectural works is strongly influenced by local climate or weather conditions. This article was written with the aim of analyzing the differences between sloping roof designs and flat roofs when applied in tropical climates such as Indonesia. Taking into account the characteristics of the typical tropical climate in Indonesia, this article will discuss in depth the advantages and disadvantages of these two types of roofs. Through a literature study, it is hoped that this article will be able to provide a more in-depth view of the benefits and challenges of each roof design in responding to Indonesia’s dynamic climate. So that it can help strengthen awareness that choosing the right roof shape is very important to create a comfortable and safe building for residents that is in accordance with the climate characteristics in Indonesia.